EFFECTS OF INSULIN PUMPS ON DIABETIC RETINOPATHY: A REVIEW - Geanina Totolici; Șerban Cristina; Carmen Tiutiuca; Kamel Earar; Dana Tutunaru (Romanian Society of Oral Rehabilitation, 2023)
With a global prevalence of 9,3% in 2019, diabetes causes eye damage, known as diabetic retinopathy, a microvascular complication and one of the leading causes of decreased visual acuity or blindness worldwide.The development of a new technology in the management of diabetes, either insulin pumps, continuous glucose monitoring devices (CGM) or augmented sensor pump therapy (SAP), has the advantage of reducing the variability in blood sugar levels, reducing of glycosylated hemoglobin levels and the episodes of severe hypoglycemia, thus increasing protection against complications such as diabetic retinopathy. Despite such important benefits, medical devices for diabetes also presents adverse effects like allergic contact dermatitis (ACD), the most important allergens being isobornyl acrylate (IBOA), rosin, ethyl cyanoacrylate and N, N-dimethylacrylamide. This review is focused on the beneficial effects of insulin pumps on diabetic retinopathy, but also on the negative effects of plastics that are part of medical devices for diabetes.